2022
DOI: 10.3389/fmed.2021.803067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNAs as New Molecular Biomarkers for Dating the Age of Wound Production: A Systematic Review

Abstract: Background:The timing of wounds production is a significant issue in forensic pathology. Although various methods have been evaluated, obtaining an accurate dating of lesions is still a challenge. The pathologist uses many parameters to value wound age, such as histological and immunohistochemical. In recent years, there have been many studies regarding the use of miRNAs in wound-age estimation; indeed, miRNAs have multiple potential uses in forensic pathology.Scope:This review aims to verify the efficacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Loss of the cutaneous continuity due to trauma may lead to serious complications and even death [ 19 ]. Therefore, determination of the wound vitality and dating is a crucial medicolegal issue, which raises the need for evaluating the well-organized wound healing sequences and the involved biomarkers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of the cutaneous continuity due to trauma may lead to serious complications and even death [ 19 ]. Therefore, determination of the wound vitality and dating is a crucial medicolegal issue, which raises the need for evaluating the well-organized wound healing sequences and the involved biomarkers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current study was also conducted to evaluate the expressions of lncFAO, which were strongly associated with healing sequences, especially inflammation resolution and tissue repair [ 5 , 20 , 32 ]. We identified its specificity in wound dating estimation and stability during early PMIs (up to 24 h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of biomolecular technology, detection methods based on nucleic acid ( 1 , 8 , 9 ), metabolites ( 10 , 11 ), and microorganisms ( 2 , 12 , 13 ) have been widely used in the past few decades. Some studies suggested that the genes, such as GAPDH2, ACTB2, 18S rRNA, miR-1, and miR-133a, are suitable indicators for estimating PMI ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are numerous forensic studies exploring available markers for the determination of wound vitality using biochemical, histochemical, immunohistochemical and molecular biological techniques ( 4 6 ). Moreover, there are several recent studies focusing on omics sciences and micro RNA ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%